Bioassays in workers exposed to long time random intakes. (February 2022) - Sánchez-León, Guillermo; López, María Antonia; Moraleda, Montserrat; Rodríguez-Díaz, Juan M.
Abstract: Workers who are occupationally exposed to radioactive aerosols are usually subjected to periodic controls of internal contamination by performing bioassays (whole body or partial body monitoring and measurement of excreta samples). The intakes are also estimated by using Static Air Samples (SAS). These measurements are used to estimate the radioactive intakes of the workers. A typical assumption is the workers are chronically (constant) exposed for long periods of time. However, the intakes are random and there are also periods without any exposure (weekends, holidays, etc.). The method presented here considers both facts. Simulations help to choose the most appropriate method of evaluation to minimize the statistical uncertainties in the intake. It has been applied to evaluate workers exposed to UO2 aerosols for a long time (30 years or more for most of them) in the same working area (sintering). Results of measurements of uranium in urine and daily intakes (from SAS) of these workers have been used. For this evaluation, the new Occupational Intakes of Radionuclides (OIR) biokinetic models of the International Commission on Radiological Protection (ICRP) for uranium have been solved. For some workers the evaluation gives a significative deviation between the intake estimated from urine samples and the intake estimated using the SAS values, supporting the idea that the physiological standard parameters of the reference worker are not always applicable. The computations have been implemented in the BIOKMOD code. Highlights: A mathematical method to evaluate internal exposures of workers exposed to multiple random intakes using bioassay has been developed. This method has been applied to workers exposed to UO2 for a long time. The evaluation gives, for some workers, a significative deviation between the intake estimated from urine samples and the intake estimated using Air Sampling. Physiological standard parameter deviations have been found in some workers. The computations have been implemented in the BIOKMOD code..